RELEVANSI GAYA KEPEMIMPINAN DENGAN KINERJA PEGAWAI, APAKAH SALING MEMPENGARUHI ? - Efendi, Ahmad Suhendra; Maruapey, Muhammad Husein; Heryati, Ade (Universitas Djuanda, 2020)
This research is motivated by the low employee work motivation, which is believed to be caused by less intensive leadership in providing guidance to lower-level employees. Therefore, the purpose of this study is to analyze the influence of leadership style on employee performance at the Department of Public Works and Spatial Planning (PUPR). The research employed an associative approach and utilized the Slovin formula for the sampling technique, resulting in a sample of 70 respondents out of a population of 167 employees. Data was collected through structured and in-depth interviews, questionnaires, and participatory observations, which were then analyzed using multiple linear regression analysis techniques. The results of the study revealed that leadership style has a significant impact on employee performance, accounting for 83.2%, while the remaining 16.8% was influenced by other variables. Based on the findings, it is recommended that the organization strive to maintain and enhance their communication skills, as the communication skills variable was found to have a dominant influence on employee performance.